Enhancing Senior High School Students’ Speaking Skills Through English Podcasts - Amalia, Risa; Novita, Dian (Teaching, Learning, and Development, 2025)
This study investigates how English podcast activities impact students' speaking skills in senior high schools, focusing on 18 participants from MA Bilingual Muslimat NU Sidoarjo, Indonesia. Using questionnaires and interviews, the research explores students' perceptions, revealing positive attitudes towards podcasts despite challenges like vocabulary limitations and speaking anxiety. The findings highlight podcasts as effective tools for enhancing speaking proficiency and motivation in English learning. The study recommends integrating podcasts in classrooms to foster creative language learning and improve student engagement. Future research can delve deeper into students' interests and experiences with applied podcasts.